2019
DOI: 10.3390/ma12071176
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Nanoparticles Rescue Rotenone-Mediated Cell Death

Abstract: The aim of the present investigation was to study the anti-oxidant effect of chitosan nanoparticles on a human SH-SY5Y neuroblastoma cell line using a rotenone model to generate reactive oxygen species. Chitosan nanoparticles were synthesized using an ionotropic gelation method. The obtained nanoparticles were characterized using various analytical techniques such as Dynamic Light Scattering, Scanning Electron Microscopy, Transmission Electron Microscopy, Fourier Transmission Infrared spectroscopy and Atomic F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…This could have been due to the strong interaction of lutein with the polymers which resulted in the absence of characteristic peaks. Similar results were observed for other nanoparticle systems [ 58 ]. Moreover, it is evident that the encapsulation of lutein did not result in any structural changes of polymers which might be attributed to either the small concentration of the drug or due to its bonding and non-bonding interactions with the surrounding matrix.…”
Section: Resultssupporting
confidence: 90%
“…This could have been due to the strong interaction of lutein with the polymers which resulted in the absence of characteristic peaks. Similar results were observed for other nanoparticle systems [ 58 ]. Moreover, it is evident that the encapsulation of lutein did not result in any structural changes of polymers which might be attributed to either the small concentration of the drug or due to its bonding and non-bonding interactions with the surrounding matrix.…”
Section: Resultssupporting
confidence: 90%
“…Biodistribution tests carried out in BalB/C mice showed that the nanoformulation mainly reached the liver, kidney, spleen, and brain, thereby being efficiently able to cross the BBB. Interestingly, an antioxidant effect of the formulation was also reported, which was attributed to the presence of chitosan, as indicated by other authors [ 130 , 133 ]. This fact could reveal a synergistic effect between fingolimod and chitosan, although more research should be conducted to clarify this potential synergistic action.…”
Section: Investigational Polymeric Nanoparticles For the Treatment Of...supporting
confidence: 62%
“…Ahlawat et al [ 133 ] evaluated the antioxidant and anti-apoptotic activities of non-loaded chitosan NPs on a human SH-SY5Y neuroblastoma cell line using RT as a neurotoxin to generate the production of ROS. Cells were exposed to chitosan NPs 6 h before being treated with RT.…”
Section: Investigational Polymeric Nanoparticles For the Treatment Of...mentioning
confidence: 99%
“…Considering the known antioxidant properties and highly sustainable nature, chitosan (CS) and ellagic acid were selected as the primary components for the enclosure and drug, respectively . CS is a biodegradable linear polysaccharide derived from chitin shells of shrimp and other crustaceans with previously documented biocompatibility, antioxidant property, and permeability-enhancing properties. EA, a polyphenol found in fruits and vegetables, possesses a wide spectrum of biological activities such as antioxidant, antiviral, anticancer, and antimutagenic properties, with potential toxicity at higher doses. , …”
Section: Introductionmentioning
confidence: 99%